2019
DOI: 10.1039/c9py01194c
|View full text |Cite
|
Sign up to set email alerts
|

Reprocessable vinylogous urethane cross-linked polyethylene via reactive extrusion

Abstract: Reactive extrusion of a precursor polymer and a diamine cross-linker leads to reprocessable vinylogous urethane polyethylene vitrimers with desired rheological properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 65 publications
3
68
2
Order By: Relevance
“…We obtain the activation energy for transesterification: E a ≈ 124 kJ/mol for PPvit. This is much higher than the quoted value for dioxaborolane metathesis, E a ≈ 16 kJ/mol, 19 and also higher than E a ≈ 108 kJ/mol for the exchange reaction of vinylogous urethanes, 21 suggesting our PPvit constitutes a more robust dynamic network.…”
Section: Journal Of Materials Chemistry a Accepted Manuscriptcontrasting
confidence: 54%
See 1 more Smart Citation
“…We obtain the activation energy for transesterification: E a ≈ 124 kJ/mol for PPvit. This is much higher than the quoted value for dioxaborolane metathesis, E a ≈ 16 kJ/mol, 19 and also higher than E a ≈ 108 kJ/mol for the exchange reaction of vinylogous urethanes, 21 suggesting our PPvit constitutes a more robust dynamic network.…”
Section: Journal Of Materials Chemistry a Accepted Manuscriptcontrasting
confidence: 54%
“…After the conception of vitrimers 12 in 2011 in the seminal work of Leibler et al, dioxaborolane metathesis 19,20 and exchange of vinylogous urethanes 21 have been employed to introduce adaptable network in TPO. In one of the earlier works by Leibler et al it was demonstrated that the network dynamics is mediated by the exchange between B-O bonds and boronic ester groups.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to real vitrimers, such weakly cross-linked thermoplasts show very limited resistance to dissolution by solvents. [66][67][68] In spite of such drawbacks, these 'vitrimerised thermoplasts' have attracted considerable attention, [66][67][68][69][70][71][72][73][74] considering the fact that they can be processed using usual thermoplastic processing techniques, while their properties can be improved in comparison to the bulk thermoplastic counterparts.…”
Section: Cross-link Density Of Vitrimer Matricesmentioning
confidence: 99%
“…1 Since then, the literature has focused on altering the exchange reaction (either catalytically controlled or catalyst-free) and adapting chemistries to different polymer backbones. 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27 Other studies explored the properties of vitrimer composites and the addition of nondynamic cross-links to the network. 14,28,29,30,31,32,33,34,35 These research efforts established that modifying vitrimer chemistry provides a pathway for tuning mechanical properties, 36,37,38 stress relaxation, 39,40,41,42 shape memory, 43,44,45 and the ability to self-heal and adhere to other materials.…”
Section: Introductionmentioning
confidence: 99%